Pengaruh Tingkat Pendidikan Ibu terhadap Prestasi Belajar Siswa Kelas I di Sanggar Belajar Kampung Baru Malaysia 2023 - Ajeng Ayu SintiaNingsih; Mandra Saragih; Suci Perwita Sari; Ismail Saleh Nasution (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The family environment is the initial education then followed by the school environment. It can be said that school is a place that is trusted by parents to receive education for quite a long time. This study aims to determine the effect of the mother's education level on the learning achievement of class I students at Sanggar Belajar, Kampung Baru Malaysia District in 2023. This type of quantitative research is with a cross sectional design. The number of samples is 15 people with total sampling technique. The results showed that there was an effect of mother's level of education on student achievement in class I with a significant value of p = 0.02 (p <0.05). Keywords:mother's educational level and student achievement